Numerical investigation of tunnel deformation due to adjacent loaded pile and pile-soil-tunnel interaction - Lueprasert, Prateep; Jongpradist, Pornkasem; Jongpradist, Pattaramon; Suwansawat, Suchatvee (My University, 2017)
An adjacent construction with a pile foundation in dense urban areas can contribute to possible damage to or an operational safety concern for existing tunnels. To establish a preventive measure in the design stage, a proper assessment method for the impacts of an adjacent pile under loading on a tunnel and an understanding of pile-soil-tunnel interaction are essential. This article recommends an assessment method for tunnel deformation, defined by the maximum extension and maximum contraction of the tunnel diameter and their associated axes with respect to the horizontal and vertical directions, respectively. The method could appropriately trace the changes to the tunnel diameter and the global distortion of the tunnel lining. Using a series of three-dimensional elasto-plastic numerical analyses conducted to investigate the influences of an adjacent loaded pile on an existing tunnel for varying pile tip positions with respect to the tunnel and soil stratum, the proposed method can effectively capture the response of the deformed tunnel as a distorted ellipse shape. Investigation of the analysis results from this assessment method in conjunction with those of the supplementary analyses of pile load reasonably reveal the pile-soil-tunnel interaction mechanism behind the tunnel deformation behaviour due to an adjacent loaded pile.
Keywords: Existing tunnel; Finite element method; Pile-soil-tunnel interaction; Tunnel deformation